A FRAMEWORK FOR EFFECTIVE JUDICIAL TRAINING AND CAPACITY BUILDING IN POST-CONFLICT COUNTRIES: ORGANIZATION-TASK-PERSON MODEL - DAYAH ABDI KULMIE; YAHYE MOHAMED JUHA; MOHAMUD DAHIR HILIF (Innovare Journal of Social Sciences, 2025)
This review comprehensively presents the need for effective judicial training for post-conflict countries or regions as they are emerging from violent conflict like civil or interstate war or significant internal strife. Due to the significance of establishing the rule of law after internal conflict for transitioning from war to peace, focusing on criminal justice, administrative law, public governance, and economic management is crucial; therefore, prioritizing the rule of law in public sector reform emerged as a new trend. In this regard, staff and institutional capacity building in these countries is an integral component for building blocks of social trust, stability, justice, and judicial service delivery and achieving sustainable peace. This paper assesses the role of judicial training and capacity building using the organization-task-person model. Understanding the interconnectedness of these three elements when planning, designing, and executing the training program is a cornerstone for effective judicial training. In other words, addressing organizational goals, knowledge, skill gaps, and job’s requirements in the four phases of the training program (training needs assessment design, delivery, and evaluation of the training program) is a key determinant of the effectiveness of the training project. Moreover, the dynamic environment of post-conflict societies necessitates establishing and capacitating judicial training institutes; and for their efficiency and sustainable impact, the paper presents three primary principles that are demanded as guides for their interventions: Learner-centered, relevance and context, and continuous learning. Equally, the paper underscores the importance of judicial training strategy and cross-sectoral collaboration for overall judicial performance, which eventually enhances justice delivery, fosters public trust, and achieves lasting peace and stability in post-conflict societies.